MgO as promoter for electrocatalytic activities of Co3O4–MgO composite via abundant oxygen vacancies and Co2+ ions towards oxygen evolution reaction. (22nd April 2023) - Laghari, Abdul Jaleel; Aftab, Umair; Tahira, Aneela; Shah, Aqeel Ahmed; Gradone, Alessandro; Solangi, Muhammad Yameen; Samo, Abdul Hanan; kumar, Mukesh; Abro, Muhammad Ishaque; Akhtar, Muhammad wasim; Mazzaro, Raffaello; Morandi, Vittorio; et al.
Abstract: Oxygen evolution reaction (OER) is known as bottleneck problem during the water splitting process due to high energy barrier and non-availability of efficient nonprecious electrocatalysts. The cobalt oxide (Co3 O4 ) in the spinel phase has limited OER activity and stability in the alkaline media. For this purpose, we have carried out the synthesis of Co3 O4 –MgO (CM) composite by wet chemical method and it offers abundant oxygen vacancies and Co 2+ concentration for the efficient OER reaction. The effect of different amounts of MgO on the OER activity of Co3 O4 was also studied. Despite inactivity of MgO towards OER, it creates high density of oxygen vacancies and favored the formation Co 2+ ions at the surface, thus accelerated the OER kinetics. The physical studies were performed to investigate the morphology, crystalline structure, surface information and chemical composition using several analytical techniques. The optimized CM-0.1 composite produced an overpotential of 274 mV at 10 mAcm −2 which is lower in value than the pristine Co3 O4 . The significant enhancement in the OER activity was verified by the large value of electrochemical active surface area values 12.8 μFcm −2 and the low charge transfer resistance of 45.96 Ω for the optimized CM-0.1 composite. The use of abundance materials for the synthesis of CM composite revealed an enhanced OER performance, suggesting the dynamic role of MgO, therefore it could be used for improving the electrochemical properties of extended range of metal oxides for specific application especially energy conversion and storage devices. Highlights: MgO has enhanced the oxygen vacancies and Co 2+ content into Co3 O4 . MgO as promoter for Co3 O4 has lowered OER overpotential. The MgO– Co3 O4 composited exhibits 274 mV overpotential at 10 mAcm −2 . The composite demonstrated fast charge transport during OER process.